Pengaruh Service Convenience Dan Service Quality Terhadap Customer Satisfaction Pada Vendor A - Kristoforus Yosef Donnyanggoro; Laurentia Verina Halim Secapramana (JURNAL ADMINISTRASI & MANAJEMEN, 2021)
This study aims to find out customer satisfaction through service quality provided by vendor A. Vendor A is a premium brand that provides photography, video graphy services engaged in the prewedding, engagement, and wedding. The variables used to measure customer satisfaction are service convenience indicators and service quality indicators. Data was collected by distributing questionnaires to 590 respondents who had used this brand documentation services in 2013-2021. Respondents have an age range of 18-40 years, with various occupational backgrounds. The sampling technique is through non-probability sampling with purposive sampling method. The results that have been obtained will be analyzed using SEM (Structed Equation Modeling) with the help of SPSS AMOS 24 software. In this study, we tested the indicators owned by service convenience (decision, access, transaction, benefit, post benefit) and service quality (tangibels, reliability, responsiveness, assurance, empathy) to customer satisfaction. The results of this study indicate that decisions have an influence on customer satisfaction, access has no effect on customer satisfaction, transactions have an influence on customer satisfaction, benefits have no effect on customer satisfaction, post benefits have an influence on customer satisfaction, tangibels have an influence on customer satisfaction, reliability does not have an effect on customer satisfaction, responsiveness has no effect on customer satisfaction, assurance has an influence on customer satisfaction, empathy has an influence on customer satisfaction. So it can be concluded that there are 6 indicators that are accepted and 4 indicators that are rejected.